1989
DOI: 10.1093/nar/17.7.2639
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the binding of transcription factor Sp1 to a single GC box recognition sequence

Abstract: The equilibrium constant was determined for the binding of the transcription factor Sp1 to a single consensus GC box DNA recognition site, (5'-GGGGCGGGGC-3'). For these experiments, single copies of the recognition site were synthesized and cloned in a standard plasmid background. Binding was measured either by a footprinting assay modified so that the binding reaction was at equilibrium, or by a gel mobility shift assay. The concentration of active Sp1 in the reactions and the dissociation constant were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
139
0
1

Year Published

1994
1994
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(155 citation statements)
references
References 23 publications
15
139
0
1
Order By: Relevance
“…4A). The choices for nucleotide substitutions were based on previous studies in which either factor binding or functional activity of the particular binding site was destroyed (3,23,24,38). These mutant enhancer fragments were subcloned into the luciferase expression vector with the minimal CD4 promoter and transiently transfected into D10 T cells, and the enhancer activity was then compared with activities unmutated enhancer constructs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A). The choices for nucleotide substitutions were based on previous studies in which either factor binding or functional activity of the particular binding site was destroyed (3,23,24,38). These mutant enhancer fragments were subcloned into the luciferase expression vector with the minimal CD4 promoter and transiently transfected into D10 T cells, and the enhancer activity was then compared with activities unmutated enhancer constructs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Selection against G was also seen for the second zinc finger of Sp1, which has the same base-contacting residues as zinc fingers 3 and 1 of the NGFI-A family (14). Additionally, there was diminished binding by Sp1 to an oligonucleotide with G at the position expected to interact with the Glu of its second zinc finger (13), and other experiments demonstrated that substitution of G for C at the same position reduced binding 30-fold (34). The nature of this interaction was not resolved by the crystal structure, but it was later suggested that a contributory influence might be an electrostatic repulsion between the O6 and N7 groups of G and the nearby Glu carboxylate oxygens, following the loss of their shell of (42).…”
Section: Discussionmentioning
confidence: 84%
“…The results of these experiments show that all three footprinted sequences are required for activation of a linked ␤-globin gene. Sp1 family members recognize a 9-bp sequence GGG GT/CG GGG (Letovsky and Dynan 1989) and thus it could be predicted that fp 2 contains two overlapping binding sites, in addition to potential weaker binding sites (Fig. 1B, wild type).…”
Section: Experimental Strategymentioning
confidence: 99%
“…Thus, we conclude that each G box contributes to the activity of fp 1-3. Because the 3Ј sequence has the best match with the Sp1 consensus binding site (Letovsky and Dynan 1989), we concentrated on this motif. For reasons of clarity, we will refer to this permutation of fp 2 as control (ct in Fig.…”
Section: Experimental Strategymentioning
confidence: 99%